Efektivitas Psikoedukasi “Bersiaga” dalam Menurunkan Tingkat Fear of Commitment pada Dewasa Awal - Widhyastuti, Cahyaning; Putri, Pradiptya Septyanti; Limin, Debby Sutanty (LPPM Universitas Informatika dan Bisnis Indonesia, 2024)
Establishing a commitment in a relationship is not easy, especially negative information about marriage relationships on social media that is very easy to access. This condition can have an impact on the feelings and perceptions of individuals in building a committed relationship, namely the emergence of feelings of fear and worry. This study aims to see how psychoeducation about marriage readiness can reduce fear of marriage in early adulthood. The study was conducted using an experimental method that provided treatment in the form of psychoeducation. Fear of marriage in this study was measured using the fear of relationship commitment scale. The results of the study showed that providing psychoeducation can reduce fear of commitment in early adults involved in the study.